Study protocol for leaving care—A comparison study of implementation, change mechanisms and effectiveness of transition services for youth - Skoog, Therése; Bergström, Martin; Karlsson, Matilda; Olsson, Tina M. (PLoS ONE, 2024)
Introduction Youth placed in out-of-home care is a large and highly vulnerable group at high risk of negative developmental outcomes. Given the size and extent of negative developmental outcomes for youth placed in out-of-home care, interventions to help this vulnerable group navigate successfully towards independent living and promote wellbeing across a spectrum of outcome areas are needed. To date, there is a lack of such interventions, particularly in Sweden. Importing interventions from other societies and cultures is associated with difficulties. The aim of the research project is to implement, test, and evaluate interventions that have been recently developed in Swedish practice to close this gap. Methods The project has an ambitious and complex data collection and analysis strategy using qualitative, quantitative, and multiple information methods (hybrid effectiveness-implementation study) over the course of two years. Both the implementation and effectiveness of the interventions will be evaluated. The recently developed My Choice-My Way! leaving care program for youth aged 15+ will be the primary focus of the project and will be compared to usual services. Conclusions The project has the potential to offer novel insights into how society can promote wellbeing across a spectrum of outcome areas for the high-risk group of youth transitioning from out-of-home care to independent living. As such, the project will have important implications for both research and practice.